Resiliensi Pada Penderita Tuna Daksa Akibat Kecelakaan - Winanda, Cahyadi; , Taufik Kasturi, M.Si., Ph.D (2016)
Purpose of the research is to understand dan describe resilient efforts of post-accident disabled people. Sample was taken by using purposive sampling. Informants of the research were 4 males with characteristics: an individual with disability because of accident and he or she can accept his or her existing condition. The research is qualitative research. Data was collected by using observation and interview. The data was analyzed descriptively. Research results show that the affecting resilience on tuna daksa sufferers namely a factor of in ourselves or internal namely informants trying to cope with the activity of like normal people other , and support from external factors namely the family especially from mother and fianc very affecting informants to forget the accident. And also support from friends and working environment which visited informants after the accident and give positive words of influential to help make informants and rise from the scene of the accident. With support of close related and important people can provide positive impact to change thinking pattern of the victims that disabled people can do nothing. The informants were able to behave as other normal people, because the close related persons always provided support and said positive things so that the informants were able to go on and to rise up from adversities after the accidents. Positive environment can help informant to stand up. The close environment such as parent, best friends and partners encouraged the informants to stand up and to live on new life. The informants had been inspired to stand up from traumatic incidents. Greatest motivation of the informants derived from normal people and also, there were some persons underestimating them. The informants wanted to prove to the persons with underestimation view that their body were incomplete but their motivation and spirit were like as normal persons or exceeding them. The informants can still work on their job as usual as pre-accident although their performances were not maximum, they felt fatigue easily because of reduced stamina.